Oxysterol‐binding protein‐related protein 2 is not essential for Phytophthora sojae based on CRISPR/Cas9 deletions. Issue 3 (6th April 2018) - Miao, Jianqiang; Li, Xiuhuan; Lin, Dong; Liu, Xili; Tyler, Brett M.
Summary: Oxysterol‐binding protein (OSBP)‐related proteins (ORPs) are a large conserved family of lipid transfer proteins in eukaryotes. In oomycetes, some ORPs are the target of the novel oomycide oxathiapiprolin. By searching the Phytophthora sojae genome database, two ORP proteins, PsORP1 (Protein ID: 558498) and PsORP2 (Protein ID: 470921), were found. Here, we investigated the biological function of PsORP2 . The expression level of PsORP2 was higher in germinated cysts and late infection than in other developmental stages. However, deletion of PsORP2 using CRISPR/Cas9 had no significant effect on sporangia production, zoospore production, cyst germination, oospore production, virulence or oxathiapiprolin sensitivity. PsORP1 also was not upregulated in Δ PsORP2 transformants. Collectively, our studies demonstrate that PsORP2 is not an essential protein for development or virulence in P. sojae under the conditions we tested.